Analgesic Efficacy of Fentanyl versus Dexmedetomidine for Postoperative Pain Management Following Posterior Spinal Stabilization Surgery: A Prospective Comparative Study at Dr. Zainoel Abidin General Hospital, Banda Aceh - Tuanku Radhi Sura; Eka Adhiany; Rozi Fadhori (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Posterior spinal stabilization is a major surgical procedure associated with significant postoperative pain. Effective analgesia is essential to prevent excessive physiological stress, hemodynamic instability, and postoperative inflammatory responses. Fentanyl and dexmedetomidine are commonly used analgesics, yet comparative evidence in posterior stabilization surgery remains inconsistent. Objective: This study aimed to evaluate the effectiveness of both agents in terms of analgesia, hemodynamic stability, and inflammatory biomarkers (NLR, PLR). Methods: A prospective comparative study was conducted on 16 patients undergoing posterior spinal stabilization at Dr. Zainoel Abidin General Hospital. Patients were allocated into two postoperative analgesia groups: fentanyl (2 mcg/kg bolus followed by 1 mcg/kg/h infusion) and dexmedetomidine (1 mcg/kg bolus followed by 0.4 mcg/kg/h infusion). Pain intensity (NRS), hemodynamics (HR, SBP, DBP, RR, SpO₂), and inflammatory markers (NLR, PLR) were assessed at 2, 6, 12, 24, and 48 hours postoperatively. Results: Baseline characteristics were comparable between groups (p > 0.05). Both groups demonstrated significant reductions in postoperative pain from 2 to 48 hours. No clinically meaningful differences in NRS were found, except at 12 hours (p = 0.011), which was not sustained at later time points. Hemodynamic parameters remained stable; differences in diastolic blood pressure at 24 and 48 hours were statistically significant but clinically negligible. NLR and PLR values decreased progressively in both groups, with no significant intergroup differences. Conclusion: Fentanyl and dexmedetomidine provide comparable analgesic efficacy, hemodynamic stability, and inflammatory modulation in postoperative management following posterior spinal stabilization. Both agents are safe and effective for postoperative analgesia in this setting.